Foam Sclerotherapy and Laser Ablation of Varicose Veins: Newer Option in Bangladesh Perspective (Cardiovascular Journal, 2018)
Background: Varicose vein is one of the most common vascular conditions in the adult population. These are conventionally treated with surgical high ligation of Sapheno-femoral junction and stripping of Great Saphenous Vein (GSV) with multiple phlebectomy. The aim of this study was to highlight the technical considerations in performing endovenous laser ablation of varicose vein, understanding the importance and role of Duplex Machine and Tumescent anesthesia with evaluation of outcome.Methods: In this retrospective study we examined the records of 297 limbs of 220 patients operated at Vascular Care Centre at Dhaka, Bangladesh between October 2013 and October 2015. Among them 1 year follow up was performed in 118 patients. Patients were contacted through telephone calls and mobile SMSs with requests for follow up.Results: Vast majority of the patients had a smooth recovery. Significant pain was present in only 10% of patients for 1week after laser therapy and 3% of patients noted bruising in thigh for 2 weeks. Among the 118 patients who reported for follow up at 12 months, 113 (96%) showed effective persistent occlusion of GSV.Conclusion: EVLA of varicose vein is gaining popularity day by day in Bangladesh. It has become established as a safe and effective treatment option for varicosities caused by GSV incompetence. Foam sclerotherapy with Sodium tetradecyl sulphate replacing the multiple phlebectomy may be a suitable adjunct. Quick return to normal activities, fewer wound infections, less leg pain and leg bruising are strongly associated with these endovenous techniques compared with Saphenous vein stripping.Cardiovasc. j. 2018; 10(2): 140-144